2021
DOI: 10.36685/phi.v7i2.409
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression, anxiety, and stress with sleep quality in Indonesian people during the COVID-19 pandemic

Abstract: Background: To prevent the spread of COVID-19, authorities implemented health protocols such as quarantine, large-scale social restrictions, and lockdowns. Data on the psychological effects and sleep quality as a result of these health protocols are still limited.Objective: This study was aimed to determine the association between depression, anxiety, and stress with sleep quality during the COVID-19 pandemic in Indonesia.Methods: An online survey was used to do a cross-sectional study among students in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…In this study, the overall magnitude of poor sleep quality among pregnant women during the era of COVID-19 was 62.8% (95% CI: 58.1-67.3). This is in line with studies conducted in Indonesia (59.5%) (18) and Northern Ethiopia (68.4%) (2). But, the magnitude of poor sleep quality in the current study was lower than in studies conducted in Turkey (88%) (26), China (87%) (11), and the United States (73%) (1).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, the overall magnitude of poor sleep quality among pregnant women during the era of COVID-19 was 62.8% (95% CI: 58.1-67.3). This is in line with studies conducted in Indonesia (59.5%) (18) and Northern Ethiopia (68.4%) (2). But, the magnitude of poor sleep quality in the current study was lower than in studies conducted in Turkey (88%) (26), China (87%) (11), and the United States (73%) (1).…”
Section: Discussionsupporting
confidence: 88%
“…Disturbed sleep during pregnancy is linked to several complications, including preeclampsia, premature birth, gestational diabetes, postpartum depression, and intrauterine growth retardation (9,13). Studies in different areas of the world reported that the prevalence of poor sleep quality among pregnant women was 17% in Peru (14), 41.2% in Vietnam (15), 43.1% in the Asian population (4), 45.7% in Canada (16), 51.8-87% in China (10,11), 53.3% in Pakistan (17), 59.5% in Indonesia (18), 73% in the United States (1). Some studies showed the prevalence of poor sleep quality among pregnant women before the pandemic in Ethiopia at Jimma medical center 30.8% (8) and Wadila primary hospital 68.4% (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the common factors reported in the literature, the novel coronavirus-2019 (COVID-19) has the potential to significantly impact both the mental and physical health of older adults. Moreover, the impacts of COVID-19 on individuals' stress and mental health have been frequently reported worldwide (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic impacts health, economic, social, and other sectors (Abas et al, 2021). The government has made efforts to reduce transmission, cases of COVID-19, and deaths by increasing herd immunity (Irnaningsih et al, 2021;Argo et al, 2021). The COVID-19 vaccination aims to achieve herd immunity in the community and protect the public from this virus (Kementerian Kesehatan Republik Indonesia, 2021).…”
Section: Introductionmentioning
confidence: 99%